Pengembangan Model Pembelajaran Deep Learning Inovatif Sebagai Pengabdian Masyarakat untuk Meningkatkan Pendidikan Inklusif di Sekolah Menengah Kejuruan Penyelenggara Pendidikan Inklusi - Andriana; Zulkarnain; Rahman, Sutisna Abdul; Widjaya, Alfred; Nasrullah, Nanang; Arrazaq, Fajar (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2023)
Inclusive education at Vocational High Schools that offer Inclusive Education (SMK-PPI) aims to provide equal access to learning for students with special needs (SBK). This community service program is designed to develop an innovative Deep Learning-based learning model to enhance inclusivity and the quality of education at SMK-PPI. The program begins with a needs identification phase, where observations and interviews are conducted at schools that accommodate SBK to understand existing challenges and identify gaps in the current teaching methods. Collaboration with the school and community stakeholders is essential to align the program's objectives and tailor the learning plan to meet specific needs. Intensive training for SMK-PPI teachers is the initial step in implementing the program, including the introduction of Deep Learning technology and the development of inclusive teaching strategies. The Deep Learning-based learning model is then implemented in classrooms involving SBK, focusing on personalized learning and using technology to meet individual students' needs. Data is continuously collected through observations, interviews, and surveys to evaluate the program's effectiveness. The evaluation results show that the model successfully increased student engagement, accessibility, and learning outcomes. Reflection and improvement are conducted based on feedback from all involved parties, ensuring that this learning model can be sustainably adopted by other schools. This program is expected to make a significant contribution to strengthening inclusive education at SMK-PPI and helping all students reach their full potential.